2013
DOI: 10.1139/cgj-2012-0467
|View full text |Cite
|
Sign up to set email alerts
|

Creep behavior in Virginia Beach sand

Abstract: Triaxial compression tests were performed on dense specimens of Virginia Beach sand at low and high confining pressures to study time effects that relate to grain crushing due to static fatigue or delayed fracture. Experiments to study effects of loading strain rate on subsequent creep showed negligible time effects and no grain crushing at low confining pressures, while tests at high confining pressures indicated increasing amounts of creep with increasing initial loading strain rates and with increasing devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Pilot tests showed that particle crushing is negligible at a confining stress of 250 kPa when compared with tests performed at a confining stress of 8000 kPa. Previous studies (Karimpour and2013) showed that particle crushing is at the root of time-dependent behavior of quartz sand. Therefore, confining pressures of 250 and 8000 kPa, with more focus on the latter, were chosen to study stress relaxation of Virginia Beach sand.…”
Section: Experimental Programmentioning
confidence: 97%
See 3 more Smart Citations
“…Pilot tests showed that particle crushing is negligible at a confining stress of 250 kPa when compared with tests performed at a confining stress of 8000 kPa. Previous studies (Karimpour and2013) showed that particle crushing is at the root of time-dependent behavior of quartz sand. Therefore, confining pressures of 250 and 8000 kPa, with more focus on the latter, were chosen to study stress relaxation of Virginia Beach sand.…”
Section: Experimental Programmentioning
confidence: 97%
“…More detailed information on specimen preparation, triaxial apparatus and testing procedure is described in Karimpour and Lade (2013).…”
Section: Page 8 Of 68mentioning
confidence: 99%
See 2 more Smart Citations
“…In this simulation, various initial strain rates were obtained in the loading phase under various creep stress levels. It can be anticipated that different creep strains will be obtained, since the amount of creep is related to the initial loading strain rates …”
Section: Experimental Validationmentioning
confidence: 99%